Impact of magnetic X-points on the vertical stability of tokamak plasmas. (1st October 2021) - Yolbarsop, A.; Porcelli, F.; Fitzpatrick, R.
Abstract: The ideal-magneto-hydro-dynamic (MHD) theory of axisymmetric modes with toroidal mode number n = 0 in tokamak plasmas is developed. These modes are resonant at the magnetic X-points of the tokamak divertor separatrix. As a consequence, current sheets form along the separatrix, which profoundly affect the stability of vertical plasma displacements. In particular, current sheets at the magnetic separatrix lead to stabilization of n = 0 modes, at least on the ideal-MHD time scale, adding an important ingredient to the mechanism of passive feedback stabilization.